2008
DOI: 10.1007/s00296-008-0676-7
|View full text |Cite
|
Sign up to set email alerts
|

Normal levels and function of endothelial progenitor cells in patients with psoriatic arthritis

Abstract: Endothelial progenitor cells (EPCs) are a population of bone marrow derived cells which have been attributed with the ability to migrate into areas of tissue ischemia and to posses reparative qualities. EPCs have been shown to be decreased in level and function in various inflammatory disorders. Psoriasis and psoriatic arthritis are associated with an increase in cardiovascular morbidity. The aim of the study was to investigate the number of EPCs among patients suffering from psoriasis and psoriatic arthritis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 23 publications
3
33
1
Order By: Relevance
“…CD133+/KDR+ progenitor cells have been demonstrated to differentiate in endothelial cells both in vitro and in vivo, contribute to reendothelialization of left ventricular assist devices and promote endothelial regeneration in sites of ischemia and vascular injury in humans [17,18]. Contrary to our method, Ablin et al [15] used another combination of surface markers that likely identifies a different subpopulation of CEPCs.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…CD133+/KDR+ progenitor cells have been demonstrated to differentiate in endothelial cells both in vitro and in vivo, contribute to reendothelialization of left ventricular assist devices and promote endothelial regeneration in sites of ischemia and vascular injury in humans [17,18]. Contrary to our method, Ablin et al [15] used another combination of surface markers that likely identifies a different subpopulation of CEPCs.…”
Section: Discussionmentioning
confidence: 66%
“…To the best of our knowledge, there is only one publication regarding the evaluation of the levels of CEPCs in patients with psoriasis. Ablin et al [15] did not show a statistically significant difference in CEPCs numbers between patients with psoriasis (n = 9), psoriatic arthritis (n = 22) and controls (n = 16). In their study CEPCs were identified as CD133+/CD34+ and CD34+/KDR+ cells in peripheral blood with flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating EPC represents a population of bone marrow‐derived cells from peripheral blood that contributes to vascular genesis and repair and has been shown to be depleted in patients with systemic inflammatory disease . A study involving 32 patients with psoriasis (with or without arthritis) showed no significant difference of CD34 + /133 + EPC and CD34 + /KDR + EPC compared with controls . Conversely, a study involving 21 patients with mild degree of psoriasis demonstrated that CD34 + /KDR + and CD34 + /CXCR4/KDR + were lower compared with controls .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence is emerging to emphasize the role of endothelial progenitor cells (EPC) to maintain vascular endothelial integrity and measurement of circulating EPC can be used as a biomarker to determine subclinical atherosclerosis . Studies that evaluate circulating levels of EPC in patients with psoriasis compared with controls are however conflicting . Further, the role of EPC in relation with atherosclerosis in these patients has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…41 However, the study had limited statistical power, and mean hemangioblastic EPC levels were found to be 29% lower in PsA patients compared with healthy controls (0.025% versus 0.035% of the blood population relative to mononuclear cells) but not psoria sis patients without articular involvement (0.019%). Perhaps EPC levels are affected by the formation of psori atic lesions but not by accompanying arthritis.…”
Section: Epc Levels In Psoriatic Arthritismentioning
confidence: 97%